Critical Analysis of Victims of Sexual Harassment in Criminal Law - Halda Septiana Purwinarto; Ismunarno Ismunarno; Ferry Irawan Febriansyah (Jurnal Hukum dan Pembangunan Ekonomi, 2024)
Sexual harassment is a deviant behavior in society, where the perpetrator does something that is indecent, unethical, detrimental, and traumatizing to the victim. Sexual harassment is also known as an act of exploitation, intimidation, and coercion against its victims, both men and women. There are many things that lead to sexual harassment, such as the habit of the public to wear open clothes, especially women, so that this becomes a widespread accusation in society that causes deep trauma for the victims. This study aims to analyze victims of sexual harassment in criminal law, including the causes, impacts, and efforts to reduce this case. Overcoming sexual harassment requires various struggles from various parties. The existence of comprehensive and directed sex education must be regulated by the community from an early age and given knowledge about awareness, understanding, and respect for individual rights. A strong legitimacy system must also be implemented to deal decisively with perpetrators of sexual harassment and provide adequate support and an approach to victims. Acts of sexual harassment have been regulated in the Criminal Code Number 1 of 2023, articles 414 to 422.